2020
DOI: 10.3390/cells9102257
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Locus 15q24.1 Reveals a Gender-Specific Association with Neovascular but Not Atrophic Age-Related Macular Degeneration (AMD)

Abstract: Genome-wide association studies (GWAS) have identified an abundance of genetic loci associated with complex traits and diseases. In contrast, in-depth characterization of an individual genetic signal is rarely available. Here, we focus on the genetic variant rs2168518 in 15q24.1 previously associated with age-related macular degeneration (AMD), but only with suggestive evidence. In a two-step procedure, we initially conducted a series of association analyses to further delineate the association of rs2168518 wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…As a consequence, small allele-specific regulatory effects may only become apparent with an increase in target gene expression or by effects accumulating with age. This would also fit with the associations found for hsa-miR-4513 and its seed polymorphism rs2168518 with age-related phenotypes such as cancer ( 8–11 ), cardiovascular conditions ( 12–15 ) and age-related macular degeneration ( 15 , 16 ). In summary, allele-specific regulation of CDKN2A by hsa-miR-4513-A is a promising mechanism that could explain the association of the miRNA locus with seemingly unrelated age-related pathologies.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…As a consequence, small allele-specific regulatory effects may only become apparent with an increase in target gene expression or by effects accumulating with age. This would also fit with the associations found for hsa-miR-4513 and its seed polymorphism rs2168518 with age-related phenotypes such as cancer ( 8–11 ), cardiovascular conditions ( 12–15 ) and age-related macular degeneration ( 15 , 16 ). In summary, allele-specific regulation of CDKN2A by hsa-miR-4513-A is a promising mechanism that could explain the association of the miRNA locus with seemingly unrelated age-related pathologies.…”
Section: Discussionsupporting
confidence: 70%
“… Results of literature text searches relating allele-specific hsa-miR-4513 target genes with phenotypes. Various phenotypes have been reported in the literature to which hsa-miR-4513 or its seed polymorphism rs2168518 have been linked, including cancer ( 8–11 , 17 ), cardiovascular phenotypes ( 12–15 ), age-related macular degeneration ( 15 , 16 ), diabetes ( 12 ), metabolic products in urine ( 15 ) and several lipid traits ( 12 ). The online databases OMIM ( 19 ) and MGI ( 22 ) were searched to assign allele-specific target genes to individual phenotype groups by specific keywords defined as follows: ‘cell proliferation’ or ‘cell death’ (cancer), ‘cardiovascular system’ (cardiovascular phenotypes), ‘vision/eye’ (age-related macular degeneration), ‘cellular glucose’ or ‘insulin resistance’ (diabetes), ‘homeostasis/metabolism’ and ‘renal/urinary system’ (metabolic products in urine) and ‘lipid binding’ (lipid traits).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This significant association was evident in both nonexudative and exudative AMD subgroups 7 . The relationship between AMD and cardiovascular disease is supported by genetic studies that the pleiotropic 15q24.1 association signal may have a shared mechanism between blood pressure regulation and choroidal neovascularization with a potential involvement of CYP1A1 8 . Further genetic evidence from a total of 33,526 individuals predominantly of European ancestry from the International Age-related Macular Degeneration Genomics Consortium showed that increasing HDL-cholesterol (particularly via CETP inhibition) is a causal risk factor for AMD and that increasing HDL-cholesterol will increase AMD risk 9 .…”
Section: Introductionmentioning
confidence: 98%